2013
DOI: 10.1558/cj.v24i1.59-75
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chat Room Productivity

Abstract: Language production of Spanish students using synchronous CMC (chat) during class time was compared with that of students meeting outside of class. The study included about 100 participants enrolled in 10 sections of a first-quarter Spanish course at a US university. Students in the control group spent 30 minutes of their weekly class time in computer labs completing a chat room assignment. Students in the experimental group planned their own schedules for meeting 30 minutes each week, outside of class time, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This echoes earlier findings about the effect of the writing-like aspects of text chat as well as the emerging visual transcript of the communication which enables learners to focus on their language (Sanders, 2006;Deusen-Scholl, Frei, & Dixon, 2005). While this may push learners to make form-meaning connections in text chat (Doughty & Long, 2003), factors such as the speed of text exchange in text chat may also reduce opportunities to attend to linguistic complexity compared to pen-and-paper collaborative writing.…”
Section: Complexitysupporting
confidence: 80%
“…This echoes earlier findings about the effect of the writing-like aspects of text chat as well as the emerging visual transcript of the communication which enables learners to focus on their language (Sanders, 2006;Deusen-Scholl, Frei, & Dixon, 2005). While this may push learners to make form-meaning connections in text chat (Doughty & Long, 2003), factors such as the speed of text exchange in text chat may also reduce opportunities to attend to linguistic complexity compared to pen-and-paper collaborative writing.…”
Section: Complexitysupporting
confidence: 80%
“…For example, studies of computer-mediated communication (CMC) have been fruitful in research on instructed second language acquisition, but have also given insight into how learners use CMC in out-of-class settings. For example, Sanders (2006) showed that out-of-class online chat led to more language production than in-class chat. Noting that most research on negotiation of meaning in L2 interaction had been conducted among L2 users and under experimental conditions, Tudini (2007) investigated negotiation of meaning in online interactions between learners of Italian and native speakers.…”
Section: How Do Learners Learn Beyond the Classroom?mentioning
confidence: 99%
“…Advances in technology have enabled and facilitated distance education practices, many of which have been integrated into the design of traditional courses. In fact, examples of distance education practices i in classroom-based courses (e.g., chat, as discussed in Abrams, 2003;Chun, 1994;Sanders, 2006) are so common that they may not be immediately recognizable as hallmarks of distance teaching: assignments are delivered by email, post-lecture discussions are conducted on online message boards, or course literature is accessed via the Internet. The first step in the creation of a distance course or program, or the transformation of existing, campus-based courses or programs, is therefore often (mis)understood as an exercise in fully incorporating these and similar practices into the course or program design.…”
Section: Background To the Studymentioning
confidence: 99%